The constitutionality of the Maiden Bursary - Mdutywa, Asiphe (Department of Public Law, 2023)
The South African Constitution and the Convention on the Elimination of All Forms of Discrimination Against Women and other international law instruments are missioned to ensure the advancement and protection of women by eradicating discriminatory actions targeting women, on any platform. The introduction of the Maiden Bursary, to advance the futures of young women, seeks to empower women. However, the process of achieving this advancement perpetuates negative gender stereotypes and a safe haven for discrimination. Therefore, this thesis unpacks the constitutionality and assesses the extent to which the bursary may limit constitutional rights such as equality and dignity. This thesis roots its argument on case law, legislation, and existing literature on virginity testing.